Four Compounds Isolated from Polygonum lanatum Roxb - Akter, Taslima; Siddiqi, M Mahboob Ali; MA, Al-Mansur; Sohrab, MH; Chowdhury, AM Sarwaruddin; Hasan, Choudhury M (Dhaka University Journal of Science, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/dujs.v61i2.17074 Dhaka Univ. J. Sci. 61(2): 213-214, 2013 (July)